Comparison of high-volume and high-intensity upper body resistance training on acute neuromuscular performance and ratings of perceived exertion - da Silva, B. V. C.; Branco, D. B. T.; Ide, B. N.; Marocolo, M.; de Souza, H. L. R.; Arriel, R. A.; Oranchuk, D. J.; Mota, G. R. (International Journal of Exercise Science, 2020)
The assessment of neuromuscular fatigue is important for minimizing the risks of nonfunctional overreaching, and monitoring training loads has rapidly grown in recent years. The objective of the study was to compare the acute upper body performance and rating of perceived exertion (RPE) responses to high-volume (HV) and high-intensity (HI) resistance-training loads. Sixteen young resistance-trained men (4 repetition maximum [RM] bench press = 105.8 ± 15.9 kg) were divided into two groups of eight subjects each that performed a HI (3 sets of 4RM with 180 s of rest), and a HV (4 sets of 12RM with 90 s of rest) training sessions. Session RPE was obtained 30 min Post. The medicine-ball throw (MBT) performance was measured at pre, and 10 min post. Training volume load (movements × load), and intensity (volume load ÷ movements) were calculated. Volume load was significantly higher for HV (10890 ± 1241 kg) than HI (2718 ± 413 kg) protocol (p < 0.001). Intensity was significantly higher for HI (100.7 ± 15.3 kg) than HV (75.6 ± 8.6 kg) protocol (p = 0.002). MBT performance was significantly reduced from pre- to post- HV (p < 0.001; Delta = -11%), but not in HI (p = 0.15; Delta = -5%). RPE was significantly higher Post-HI (9.9 ± 0.4) than Post HV (8.9 ± 0.8) (p = 0.01). We conclude that higher volume loads induce greater upper body neuromuscular fatigue in young resistance-trained men. Session RPE may reflect training intensity, but not the performance impairments.